Practical variable speed drives and power electronics - Barnes, Malcolm (Practical professional books from Elsevier., 2003)
Typical practical applications of VSDs in process control and materials handling, such as those for pumping, ventilation, conveyers, compressors and hoists are covered in detail.?Provides a fundamental understanding of the installation, operation and troubleshooting of Variable Speed Drives (VSDs)?Includes practical coverage of key topics such as troubleshooting, control wiring, operating modes, braking types, automatic restart, harmonics, electrostatic discharge and EMC/EMI issues?Essential reading for electrical engineers and those using VSDs for applic.